الفهرس - بن مشري, عبد الحليم (Revue jurisprudence, 2019)
Conditions of publication in jurisprudence Journal 1. The Journal of jurisprudence, is a periodic scientific journal published by the laboratory of the effect of the Jurisprudence on the Movement of Legislation, University of Muhammad Khidr Biskra, since 2004, with international numbering (ISSN: 8615 - 1112), approved by the General Direction of scientific research and technological development, since December 2016, issued periodically (half -yearly), with the possibility of publishing special numbers. 2. The Journal publishes research related to the field of rights and law in the three languages ​​ (Arabic, French or English). 3 - The article submitted for publication must not have been published or submitted for publication in other places, or participated in a forum or be part of a book or a thesis or a university thesis. 4 - The number of search pages should not exceed 25 pages, and not less than 12 pages, counting the references, margins and supplements, if any. 5 - The research must be accompanied by a summary that does not exceed 150 words in the language in which the research was written, and another summary of the same size in a different language (English, French or Arabic). 6 - Write under the title of the research directly: the name, title and scientific degree and the area to which the researcher belongs. 7 - The journal works to review the work subject to double scientific expertise, and sent back to the researcher for correction, if any, and can not be included in the work of the journal only after reviewing the language and the inclusion of the required corrections, after that, the research and articles belong to the Journal, and the researcher can not claim to return Or re-published only after approval by the management of the journal. 8. The article should take into account scientific and methodological assets that are common in academic research. 9 - The type and size of the font in the text and the margin: the line in Arabic simplified Arabic in size (14), in the margin size (12). The font in foreign language Times New Roman, in the text size (12), in the margin size (10), also must adopt 01 cm between lines, page edges (top 02 cm, bottom 02 cm, right 03 cm, left 02 cm). The margins are at the bottom of each page of the article in the automatic way. The list of sources and references should be mentioned at the end of the article. 10 - Articles published in the Journal of jurisprudence do not necessarily reflect the opinion of the journal, and any breach by one of the researchers to scientific ethics subject him to the legal texts related to the plagiarisme . An article in violation of the above terms, is not subject to arbitration and publication, and the journal is not obliged to notify the sender in this case. 11. The article to be published will be submitted electronically through the National Platform www.asjp.cerist.dz by selecting the Journal of Jurisdiction, and send the article to the Review; on the link https://www.asjp.cerist.dz/en/PresentationRevue/124